2018
DOI: 10.1038/s41467-018-04775-8
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional free riders do not free ride on punishment

Abstract: Strong reciprocity explains prosocial cooperation by the presence of individuals who incur costs to help those who helped them (‘strong positive reciprocity’) and to punish those who wronged them (‘strong negative reciprocity’). Theories of social preferences predict that in contrast to ‘strong reciprocators’, self-regarding people cooperate and punish only if there are sufficient future benefits. Here, we test this prediction in a two-stage design. First, participants are classified according to their disposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 68 publications
(66 reference statements)
7
31
1
Order By: Relevance
“…Secondparty punishment (SPP) might be inflicted to increase future personal benefits by deterring the offender's repeated selfish behaviors [14]. Previous empirical studies have found that when an individual's personal interests are harmed by defection, even those who have defected themselves tend to punish the defector in the same manner as those who have not defected [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Secondparty punishment (SPP) might be inflicted to increase future personal benefits by deterring the offender's repeated selfish behaviors [14]. Previous empirical studies have found that when an individual's personal interests are harmed by defection, even those who have defected themselves tend to punish the defector in the same manner as those who have not defected [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Our setup enables us to classify individual participants according to how their punishment decisions respond to descriptive norms, thereby deepening empirical understanding of individual differences in (conditional) punishment. Individual differences in conditional cooperation have received considerable attention in prior research, indicating that the dynamics of cooperation in groups strongly depend on the interplay of individuals' conditional strategies and their beliefs about others' cooperativeness (40,50,51). In sharp contrast, little is known about individual differences in conditional punishment and the way in which these differences may affect the emergence of cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies have revealed that monetary and social reward share similar neural mechanisms (6). In laboratory research, cooperative behaviors were significantly elevated when the subjects' choices were associated with the costs of monetary benefits (7,8), social reputation (5,9) or both (10,11). For example, PGG studies demonstrated that financial punishment can strongly elevate contribution (12), even in dispositional free riders (8).…”
Section: Introductionmentioning
confidence: 99%